Sosialisasi dan Pelatihan Keuangan Wirausaha bagi Para Penenun Ulos di Desa Sigaol Timur, Kecamatan Uluan, Kabupaten Toba, Sumatera Utara - Hanna Meilani Damanik; Martin Luter Purba; Hendrik E. S Samosir; Halomoan Sihombing; Bonifasius Tambunan (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
The purpose of this community service is to provide a better understanding of Ulos weaving business actors in Sigaol in order to make regular business financial administration and to provide knowledge to Ulos weaving business actors in order to make business financial planning effectively. The method used is to introduce and socialize community service programs to ulos weavers to convey the background and objectives of the activity, introduction and training in making business plans, making profit and loss statements, balance sheets and financial reports and conducting evaluations to determine the success of the training that has been given to Ulos weavers. The ulos weavers in Sigaol Timur Village are still in the stage of starting their business and are currently included in the MSME group. Currently there are around 20 weavers who are members of the Bintang Maratur Ulos Weaving Group. This community service activity was carried out well and is expected to provide an outcome where the ulos business owners in Porsea and their employees get motivation and are expected to increase their competence, especially in terms of financial management so that they can have a higher competitive advantage.